(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2022)
The aim of the article is an attempt to indicate the place and role of spirituality and religion in the period of the emergence and construction of the ideological foundations of Polish Scouting. Spiritual and religious education in the movement was the result of the partitioned reality in which the Catholic faith united the Polish nation, and the military and military character of scouting was to strengthen the fighting spirit of the young generation for an independent homeland.